Rajko Ložar - upravnik Etnografskega muzeja 1940-1945 - Ložar-Podlogar, Helena (Etnolog. Nova vrsta (Ljubljana), 2003)
Rajko Ložar, the wartime director of the Ethnographic Museum in Ljubljana and an archaeologist by education, was also active as an art historian, ethnologist and literary critic, and he was a prominent figure in the country's cultural life before the Second World War. This article presents the period in which he was the museum's director, based on his autobiographic notes. In these notes Ložar sheds light on the beginnings of the ethnographic collections in the National Museum, the work of the museum's first director Niko Zupanič, and the staff who worked in the museum in the difficult wartime conditions after Zupanič became a university professor and his place was taken by Lozar, who until then had been a curator at the National Museum for 12 years. Beside collecting objects in the field, purchasing and taking over individual collections, the museumćs activities centred around publishing Narodopisje Slovencev (The Ethnology of the Slovenes) and the journal Etnolog,and its co-operation in the project Obnova slovenske vasi (Renovation of the Slovene village). In 1945 Rajko Ložar was forced to withdraw into exile.
Keywords: Ložar, Rajko, 1904-1985; Slovenski etnografski muzej; Ljubljana; etnologi; biografije; Slovenia; Slovenija